2011
DOI: 10.1007/s11240-011-9931-9
|View full text |Cite
|
Sign up to set email alerts
|

Annatto pigment production in root cultures of Achiote (Bixa orellana L.)

Abstract: Bixa orellana L. is a tree native to South America known for its reddish orange pigment 'annatto' produced only on the aril portion of its seeds. It is the most preferred natural food colorant next to saffron, having wide applications in the dairy industry and also as a cosmeceutical. Normal root cultures of B. orellana were established under in vitro conditions on Murashige and Skoog (MS) medium containing a-naphthaleneacetic acid (NAA), indole-3-butyric acid (IBA) and indole-3-acetic acid (IAA) at 0.05-0.2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
(14 reference statements)
1
10
1
Order By: Relevance
“…In contrary to the present study Mahendranath et al, (2011) reported that when the combination of NAA with IBA was used there was no significant improvement in root biomass compared to individual treatment of respective auxins in Bixa orellana. In another study, MS liquid medium supplemented with IBA and IAA combination led to one and half fold increase of root production from cotyledon derived calli of Withania somnifera (Sivanandhan et al, 2012).…”
Section: Adventitious Root Induction and Proliferation From In Vitro contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrary to the present study Mahendranath et al, (2011) reported that when the combination of NAA with IBA was used there was no significant improvement in root biomass compared to individual treatment of respective auxins in Bixa orellana. In another study, MS liquid medium supplemented with IBA and IAA combination led to one and half fold increase of root production from cotyledon derived calli of Withania somnifera (Sivanandhan et al, 2012).…”
Section: Adventitious Root Induction and Proliferation From In Vitro contrasting
confidence: 99%
“…It was noted in the adventitious root culture of Decalepis arayalpathra (Sudha and Seeni, 2001) and in the adventitious root culture of Aloe vera (Lee et al, 2011) callusing of roots in the presence of NAA and less number of lateral roots decreased the biomass, but IBA combination resulted in increased biomass accumulation. Prolonged cultures of explants in NAA and IBA with higher level of concentrations did not result in root production as observed in Bixa orellana (Mahendranath et al, 2011) and in Periploca sepium (Zhang et al, 2011) from in vitro leaf derived roots.…”
Section: Adventitious Root Induction and Proliferation From In Vitro mentioning
confidence: 76%
See 1 more Smart Citation
“…Further, the purity of the obtained bixin was confirmed through ultraviolet visible spectrophotometry, Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR) spectroscopy. High performance liquid chromatography (HPLC) analysis of bixin was carried out as per the protocol of Mahendranath et al (28). Similarly, the isolation and characterization of norbixin were performed as already described in our previous report (29).…”
Section: Preparation Of Bixin and Norbixinmentioning
confidence: 99%
“…Aparecido et al (Equations 2 to 7), with an available water-storage capacity (WS) of 100 mm. This WS was used due the root system of the urucum attain up to 100 cm (Barbieri et al 2011;Mahendranath et al 2011). …”
Section: Methodsmentioning
confidence: 99%